IMPLEMENTASI PROGRAM KARTU INDONESIA PINTAR DALAM UPAYA PEMERATAAN PENDIDIKAN SEKOLAH DASAR NEGERI - Zamaludin, M. Ega; Meigawati, Dine; Sampurna, Rizki Hegia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The purpose of this study was to determine the implementation of the Smart Indonesia Card program in Efforts to Equalize Public Elementary School Education in Cikole District, Sukabumi City for the 2021/2022 Period. And to find out the supporting and inhibiting factors in the Implementation of the Smart Indonesia Card Program in the Education Equality Activities of Public Elementary Schools in Cikole District, Sukabumi City 2021/2022 Period. To achieve the research objectives, the researcher used a descriptive qualitative approach method. In this study, the unit of analysis that is the object or research location is an institution or agency, namely 3 elementary schools in Cikole District. The results showed that the implementation of the Smart Indonesia Card Program (KIP) in the three elementary schools was in accordance with the implementation instructions set by the Ministry of Education and Culture. The KIP program is intended for children aged 6-12 years from poor, vulnerable poor families, and families receiving other social programs. The amount of KIP program funds received by students ranged from 225,000 to 450,000 rupiah per year. The implementation of this program is considered successful in the effort to equalize education, especially in reducing the possibility of students dropping out due to financial constraints.